Calidad de servicio y satisfacción del cliente en Intensas Salón y Spa Iquitos, 2023 - Abanto Soplin, Segundo Jose (2024)
The purpose of this study was to examine the relationship between service quality and customer satisfaction at Intensas Salon & Spa during the year 2023. The study population consisted of 40 users who utilized the customer service, resulting in a Pearson correlation coefficient of 0.700 with a two tailed significance value of 0.000. The findings indicated a general acceptance of the hypothesis. In 2023, a moderate yet significant correlation (0.700**) was found between variables at Intensas Salon & Spa. The study revealed that 62.50% of customers rated the service quality positively, while 63% categorized customer satisfaction as average. The average respondent ratings for the variables were 0.700 in the Pearson correlation, with a two-tailed significance value of 0.000, suggesting the need for improvements.